NFκB and Kidney Injury - Song, Ning; Thaiss, Friedrich; Guo, Linlin (Frontiers in Immunology, 2019)
Abstract: The global burden of chronic kidney disease will increase during the next century. As NFκB, first described more than 30 years ago, plays a major role in immune and nonimmune-mediated diseases and in inflammatory and metabolic disorders, this review article summarizes current knowledge on the role of NFκB in in vivo kidney injury and describes the new and so far not completely understood crosstalk between canonical and non-canonical NFκB pathways in T-lymphocyte activation in renal disease.